LOS TRABAJOS ACADÉMICOS: REFLEXIÓN SOBRE LA COMPRENSIÓN LECTORA EN ESTUDIANTES DE EDUCACIÓN BÁSICA EN TUNGURAGUA - ANALUISA FLORES LIDA JANETH (2025)
Reading teaching, as a cultural process, must be broader than in the past, since it must meet the increasing demands of contemporary life. The objective of the research was to determine how reading comprehension impacts academic work in basic education students in Tungurahua. The type of research is descriptive explanatory with a quantitative approach to analyze the relationship between reading comprehension and academic work. The study population consisted of 62 7th grade EGB students. The results showed that important characteristics were evident in relation to academic work, taking the summaries and paraphrases that the students elaborate, which are evident as weak in their development, limiting the cognitive process, and also showing insufficient analytical capacities in the argumentation they make, showing inadequate critical reading. Certain elements that are present in reading comprehension were identified, which are points that should be given special treatment, such as the coherence and cohesion of the structure of academic works, as well as the lack of originality in the analysis of content that students present in their works. It is concluded that the way in which the variables Reading Comprehension and Academic Works are related is significantly positive, the correlation obtained was Rho = 0.821, which establishes a high relationship between the variables and that adequate and pertinent reading comprehension impacts on academic works, explaining it by 67.40%.